2011
DOI: 10.1007/s00774-010-0250-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound bone mass in patients undergoing chronic therapy with oral anticoagulants

Abstract: The purpose of this study was to assess the effects of chronic oral anticoagulant (OAC) treatment on bone mass using quantitative ultrasound (QUS) techniques. A total of 120 patients (47 women and 73 men) undergoing treatment with OAC and 57 healthy subjects (27 women and 30 men) participated in this study. Bone status was assessed using QUS devices that measure the amplitude-dependent speed of sound (Ad-SoS) in phalanges and the broadband ultrasound attenuation (BUA) in the calcaneus. Men undergoing OAC treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
7
0
1
Order By: Relevance
“…including secondary causes of osteoporosis) were collected from the electronic medical record. Medications that decrease bone mineral density include: glucocorticoids (oral and inhaled), antiasthma (only budesonide/formoterol, fluticasone/salmeterol), anti-inflammatory (inhaled, including beclomethasone dipropionate, budesonide, ciclesonide, flunisolide, fluticasone, mometasone), anticonvulsants (only divalproex, phenytoin, carbamazepine), chemotherapeutic agents, anticoagulants, and depo-provera (Van Staa et al 2003; Chee et al 2014; Drummond et al 2008; Lee et al 2010; Brufsky et al 2008; Rey-Sanchez et al 2011; Gbolade 2002). Medications that increase bone mineral density include: denosumab, progestin only, contraceptive (systemic, levonorgesterel), bisphosphonates, androgen/anabolics (testosterone, topical or transdermal), and estrogen (transdermal, oral) (Cummings et al 2009; Caird et al 1994; Munk-Jensen et al 1988; Russell et al 2011; Rodriguez-Tolra et al 2013; Manolagas et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…including secondary causes of osteoporosis) were collected from the electronic medical record. Medications that decrease bone mineral density include: glucocorticoids (oral and inhaled), antiasthma (only budesonide/formoterol, fluticasone/salmeterol), anti-inflammatory (inhaled, including beclomethasone dipropionate, budesonide, ciclesonide, flunisolide, fluticasone, mometasone), anticonvulsants (only divalproex, phenytoin, carbamazepine), chemotherapeutic agents, anticoagulants, and depo-provera (Van Staa et al 2003; Chee et al 2014; Drummond et al 2008; Lee et al 2010; Brufsky et al 2008; Rey-Sanchez et al 2011; Gbolade 2002). Medications that increase bone mineral density include: denosumab, progestin only, contraceptive (systemic, levonorgesterel), bisphosphonates, androgen/anabolics (testosterone, topical or transdermal), and estrogen (transdermal, oral) (Cummings et al 2009; Caird et al 1994; Munk-Jensen et al 1988; Russell et al 2011; Rodriguez-Tolra et al 2013; Manolagas et al 2002).…”
Section: Methodsmentioning
confidence: 99%
“…VKA use decreases bone osteocalcin levels, which decreases bone hardness. [2][3][4] Increased blood levels of undercarboxylated osteocalcin are associated with decreased bone mineral quality, 5 but an association between VKA use and decreased bone mineral density has not been found, 6,7 suggesting that agents can affect bone structure without affecting bone density.…”
Section: Introductionmentioning
confidence: 99%
“…Our results show that significantly higher TRAP-5b levels were observed only in female players in the stress fracture group (Table 2). In contrast, it has been shown that TRAP in male and female patients taking oral anticoagulants significantly increases with a concomitant decrease in QUS 26. Although the relationship between TRAP-5b and QUS requires further clarification, these results suggest that there is an association between TRAP-5b and bone strength and/or overuse injuries in female athletes.…”
Section: Discussionmentioning
confidence: 67%